Study on Underwater Anti-washout Concrete in Sediment Environment for Offshore Engineering. Issue 2 (July 2021) - Shang, Ningning; Kang, Shaowei; Cui, Cancan; Han, Zhongzhi; Zhou, Wei; Guo, Xiaojun
Abstract: The close packing theory is used to optimize the cementitious material system of ordinary underwater anti-washout concrete, and the performance of the prepared concrete is verified through experiments. The test results show that the tightly packed underwater anti-washout concrete with C40 mix ratio is cured under the condition of seawater curing., 7d compressive strength of 31.4MPa, 28d compressive strength of 55.3MPa, 56d compressive strength of 68.7MPa, electric flux of 860C, meeting the requirements of marine engineering concrete's mechanical properties and resistance to harmful ion erosion.